High-impact high-toughness bio-based nylon composite material and preparation method thereof
By using itaconic anhydride and the third monomer graft modified elastomer, an efficient elastomer graft compatible agent is prepared, which solves the problem of insufficient impact strength and toughness of nylon materials, and achieves efficient toughening of the material and improve compatibility, expanding the scope of application.
Patent Information
- Application Number
- CN202411795835.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing nylon materials, including bio-based nylon, have insufficient impact strength, poor toughness and strong water absorption, and traditional tougheners have compatibility problems with nylon, which limits the application range of materials.
Itaconic anhydride is used as the first graft monomer, and the elastomer is grafted with the third monomer (such as butyl acrylate, α-methylstyrene, maleic anhydride) to prepare efficient elastomer grafting. Compatible agent for blending with biomass nylon to enhance its impact resistance and toughness.
It significantly improves the impact strength and toughness of nylon materials, and the impact strength is increased to 10-15 times that of pure nylon materials, while maintaining the advantages of high strength and high modulus, expanding the application range of bio-based nylon materials.
Smart Images

Figure CN119432064A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of toughening modification of nylon materials and synthesis of grafting compatibilizers, and specifically relates to a high-impact and high-toughness bio-based nylon composite material and a preparation method thereof. Background Art
[0002] Traditional nylon is mostly derived from non-renewable petroleum resources. The high temperature and high pressure production process causes high emissions of wastewater and carbon dioxide, which has a negative impact on the environment. In order to reduce the environmental burden and reduce environmental pollution, the environmental sustainability value of green fiber products has gradually become prominent, and bio-based nylon has come into being.
[0003] However, whether it is petroleum-based nylon, such as nylon 6, nylon 66, or bio-based nylon, such as nylon 56, there are problems such as insufficient impact strength, poor toughness, and strong water absorption. At present, the most common method to improve the toughness of nylon materials is to use elastomers for toughening. However, there are often compatibility issues between elastomers and nylon, which results in limited toughening effects, greatly limiting the application scope of nylon materials, especially bio-based nylon materials. At this time, elastomer compatibilizers such as POE-g-MAH and SEBS-g-MAH are often added. However, the compatibilizer grafted with maleic anhydride (MAH) has problems such as low reactivity, high volatility and pungent odor, low grafting rate (<0.8%), strong odor, and large steric hindrance of the grafted anhydride, resulting in poor compatibility and greatly reducing the toughening effect of nylon.
[0004] Therefore, how to improve the compatibility of toughening agents and nylon, such as bio-based nylon 56, so as to improve the impact resistance and toughness of nylon materials, has become a crucial technical issue with far-reaching significance and value in the field of polymer composites. Summary of the invention
[0005] The main purpose of the present invention is to provide a high-impact and high-toughness bio-based nylon composite material and a preparation method thereof, so as to overcome the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0007] The embodiment of the present invention provides a high-impact and high-toughness bio-based nylon composite material. The raw materials for preparing the nylon composite material include the following components calculated by weight: 100 parts of bio-based nylon, 0-30 parts of toughening elastomer, 0.1-30 parts of elastomer grafting compatibilizer and 0.2-0.6 parts of antioxidant; wherein the elastomer grafting compatibilizer is obtained by grafting modified elastomer with itaconic anhydride and a third monomer; the third monomer includes any one or more combinations of butyl acrylate (BA), α-methylstyrene (α-St), and maleic anhydride (MAH).
[0008] The embodiment of the present invention also provides a method for preparing the aforementioned high-impact and high-toughness bio-based nylon composite material, which comprises:
[0009] The bio-based nylon, toughening elastomer, elastomer grafting compatibilizer and antioxidant are mixed evenly, and then the obtained materials are input into a twin-screw extruder for melt blending extrusion and granulation treatment to obtain a high-impact and high-toughness bio-based nylon composite material.
[0010] An embodiment of the present invention also provides an elastomer graft compatibilizer, and the raw materials for preparing the elastomer graft compatibilizer include the following components: an elastomer, a peroxide initiator, itaconic anhydride, a third monomer and a dispersing oil; wherein the third monomer includes any one or more combinations of butyl acrylate (BA), α-methylstyrene (α-St), and maleic anhydride (MAH).
[0011] The present invention also provides a method for preparing the aforementioned elastomer graft compatibilizer, which comprises:
[0012] The elastomer, peroxide initiator, itaconic anhydride, the third monomer and the dispersing oil are uniformly mixed, and then the obtained materials are input into a twin-screw extruder for melt blending, dynamic reaction extrusion, pelletizing and homogenization to obtain an elastomer graft compatibilizer.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] (1) The present invention uses bio-based itaconic anhydride as the first grafting monomer to replace traditional maleic anhydride, which has the advantages of low boiling point, low odor, high reactivity and molecular chain flexibility. The prepared high-efficiency toughening compatibilizer not only has the effect of high-efficiency compatibility, but also can play a high-efficiency toughening effect;
[0015] (2) The elastomer / high-efficiency elastomer compatibilizer / nylon composite material prepared by the present invention not only maintains the advantages of high strength and high modulus of nylon material, but also greatly improves the toughness of nylon material, and the impact strength is increased to 10-15 times that of pure nylon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1is a diagram of the compatibility mechanism of nylon and elastomer graft compatibilizer in a typical embodiment of the present invention;
[0018] Figure 2a-2b They are respectively the trend diagrams of grafting rate of different proportions of itaconic anhydride addition and different proportions of initiator addition in the embodiments of the present invention;
[0019] Figure 3a-Figure 3b The graphs are the trend graphs of impact strength, elongation at break, tensile strength and tensile modulus of the high-impact and high-toughness PA56 in the application examples of the present invention. DETAILED DESCRIPTION
[0020] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Specifically, as one aspect of the technical solution of the present invention, it involves a high-impact and high-toughness bio-based nylon composite material. The raw materials for preparing the nylon composite material include the following components calculated by weight: 100 parts of bio-based nylon, 0-30 parts of toughening elastomer, 0.1-30 parts of elastomer grafting compatibilizer and 0.2-0.6 parts of antioxidant; wherein the elastomer grafting compatibilizer is obtained by grafting modified elastomer with itaconic anhydride and a third monomer; the third monomer includes any one or more combinations of butyl acrylate (BA), α-methylstyrene (α-St), and maleic anhydride (MAH).
[0022] In some preferred embodiments, the compatibility mechanism diagram of nylon 56 and elastomer graft compatibilizer in the present invention is as follows: Figure 1 shown.
[0023] In some preferred embodiments, the raw materials for preparing the nylon composite material include the following components calculated by weight: 100 parts of bio-based nylon, 0-30 parts of toughening elastomer, 0.1-30 parts of elastomer grafting compatibilizer, 0.1-0.3 parts of antioxidant 1010 and 0.1-0.3 parts of antioxidant 168.
[0024] In some preferred embodiments, the bio-based nylon includes any one or more combinations of PA56, PA1010, PA11, PA610, and PA410, but is not limited thereto.
[0025] In some preferred embodiments, the elastomer used to prepare the elastomer graft compatibilizer includes any one or more combinations of ethylene octene copolymer (POE), styrene-hydrogenated butadiene-styrene copolymer (SEBS), and olefin block copolymer (OBC), but is not limited thereto.
[0026] In some preferred embodiments, the toughening elastomer is the same as the elastomer used to prepare the elastomer-grafted compatibilizer.
[0027] In some preferred embodiments, the preparation method of the elastomer grafted compatibilizer includes: uniformly mixing the elastomer, peroxide initiator, itaconic anhydride, a third monomer, and a dispersing oil, and then inputting the obtained material into a twin-screw extruder for melt blending, dynamic reaction extrusion, pelletizing, and homogenization to obtain the elastomer grafted compatibilizer.
[0028] Furthermore, the mass ratio of the elastomer, the peroxide initiator, itaconic anhydride, the third monomer and the dispersing oil is 100:0.2-1:1-9:0.5-3:0.5-2.
[0029] Further, the elastomer includes any one or more combinations of ethylene octene copolymer (POE), styrene-hydrogenated butadiene-styrene copolymer (SEBS), and olefin block copolymer (OBC), but is not limited thereto.
[0030] Further, the peroxide initiator includes any one or more combinations of 2,4-di-tert-butyl peroxide isopropylbenzene (BIBP), diisopropyl peroxydicarbonate (DIPP), di-tert-butyl peroxide (DTBP), and tert-butyl peroxyacetate (TBPA), but is not limited thereto.
[0031] Furthermore, the dispersing oil includes any one or more combinations of white oil, epoxidized soybean oil, and paraffin oil, but is not limited thereto.
[0032] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned high-impact and high-toughness bio-based nylon composite material, which comprises:
[0033] The bio-based nylon, toughening elastomer, elastomer grafting compatibilizer and antioxidant are mixed evenly, and then the obtained materials are input into a twin-screw extruder for melt blending extrusion and granulation treatment to obtain a high-impact and high-toughness bio-based nylon composite material.
[0034] In some preferred embodiments, the process parameters adopted by the twin-screw extruder include: the temperature of zone 1 is 130-150°C, the temperature of zone 2 is 220-240°C, the temperature of zone 3 is 230-250°C, the temperature of zone 4 is 240-270°C, the temperature of zone 5 is 245-265°C, the temperature of zone 6 is 245-265°C, the temperature of zone 7 is 245-265°C, the temperature of zone 8 is 240-260°C, the temperature of zone 9 is 240-260°C, the temperature of zone 10 is 245-260°C, the temperature of zone 11 is 245-260°C, the length-to-diameter ratio of the screw adopted is 42:1-52:1, the screw speed is 200-400rpm, and the feeding frequency is 50-70Hz.
[0035] In some more specific embodiments, the method for preparing the high-impact and high-toughness bio-based nylon composite material comprises the following steps:
[0036] (a) mixing the raw materials of bio-based nylon, toughening elastomer, elastomer grafting compatibilizer, antioxidant 1010 and antioxidant 168 uniformly according to the mass fractions mentioned above, and adding the mixture into a twin-screw extruder for melt blending, extrusion and granulation;
[0037] (b) The extruded material is cooled by water in a cooling water tank and air-cooled by a blow dryer, and then uniformly pelletized and homogenized to prepare a high-impact and high-toughness bio-based nylon material.
[0038] Furthermore, the extrusion temperatures are 130-150°C for zone 1, 220-240°C for zone 2, 230-250°C for zone 3, 240-270°C for zone 4, 245-265°C for zone 5, 245-265°C for zone 6, 245-265°C for zone 7, 240-260°C for zone 8, 240-260°C for zone 9, 245-260°C for zone 10, and 245-260°C for zone 11. The screw length-to-diameter ratio used in twin-screw melt extrusion is 42:1-52:1, the screw speed is 200-400rpm, and the feeding frequency is 50-70Hz.
[0039] Another aspect of an embodiment of the present invention further provides an elastomer graft compatibilizer, and the raw materials for preparing the elastomer graft compatibilizer include the following components: an elastomer, a peroxide initiator, itaconic anhydride, a third monomer and a dispersing oil; wherein the third monomer includes any one or more combinations of butyl acrylate (BA), α-methylstyrene (α-St), and maleic anhydride (MAH).
[0040] In the present invention, itaconic anhydride has the advantages of high boiling point, high reactivity, high molecular chain flexibility and bio-based compared with MAH, so the elastomer compatibilizer described in the present invention has the advantages of high grafting rate, low odor, high compatibility effect and high toughening compared with the existing mature commercial elastomer grafted maleic anhydride (MAH), such as POE-g-MAH and SEBS-g-MAH. The bio-based nylon material toughened with elastomer and elastomer grafted compatibilizer has the advantages of high impact resistance and high toughness, which greatly solves the disadvantage of insufficient toughness of nylon materials and expands the application range of bio-based nylon materials.
[0041] In some preferred embodiments, the raw materials for preparing the elastomer graft compatibilizer include the following components calculated by weight: 100 parts of elastomer, 0.2-1 parts of peroxide initiator, 1-9 parts of itaconic anhydride, 0.5-3 parts of third monomer and 0.5-2 parts of dispersing oil.
[0042] In some preferred embodiments, the elastomer includes any one or more combinations of ethylene octene copolymer (POE), styrene-hydrogenated butadiene-styrene copolymer (SEBS), and olefin block copolymer (OBC), but is not limited thereto.
[0043] In some preferred embodiments, the peroxide initiator includes any one or more combinations of 2,4-di-tert-butyl peroxide isopropyl benzene (BIBP), diisopropyl peroxydicarbonate (DIPP), di-tert-butyl peroxide (DTBP), and tert-butyl peroxyacetate (TBPA), and is not limited thereto.
[0044] In some preferred embodiments, the itaconic anhydride is produced by dehydrating agricultural byproducts such as starch, sucrose, sawdust or straw through biological fermentation.
[0045] In some preferred embodiments, the dispersing oil includes any one or more combinations of white oil, epoxidized soybean oil, and paraffin oil, but is not limited thereto.
[0046] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned elastomer graft compatibilizer, which comprises:
[0047] The elastomer, peroxide initiator, itaconic anhydride, the third monomer and the dispersing oil are uniformly mixed, and then the obtained materials are input into a twin-screw extruder for melt blending, dynamic reaction extrusion, pelletizing and homogenization to obtain an elastomer graft compatibilizer.
[0048] In some preferred embodiments, the process parameters adopted by the twin-screw extruder include: the temperature of zone 1 is 130-150°C, the temperature of zone 2 is 140-160°C, the temperature of zone 3 is 160-180°C, the temperature of zone 4 is 170-190°C, the temperature of zone 5 is 170-190°C, the temperature of zone 6 is 175-195°C, the temperature of zone 7 is 175-195°C, the temperature of zone 8 is 170-190°C, the temperature of zone 9 is 170-190°C, the temperature of zone 10 is 170-185°C, the temperature of zone 11 is 170-185°C, the temperature of zone 12 is 165-185°C, the length-to-diameter ratio of the screw adopted is 42:1-52:1, the speed of the main screw is 200-400rpm, and the speed of the feeding screw is 20-40rpm.
[0049] In some more specific embodiments, the method for preparing the elastomer grafted compatibilizer comprises the following steps:
[0050] (a) after uniformly mixing the elastomer and the dispersing oil according to the aforementioned mass fractions, adding the peroxide initiator, itaconic anhydride and the third monomer and mixing again;
[0051] (b) adding the uniformly mixed materials into a twin-screw extruder for melt blending and dynamic reaction extrusion;
[0052] (c) The extruded material is water-cooled or air-cooled, cut into particles of uniform size by a pelletizer, and finally homogenized for 2-4 hours.
[0053] Furthermore, the extrusion temperatures are 130-150°C for zone 1, 140-160°C for zone 2, 160-180°C for zone 3, 170-190°C for zone 4, 170-190°C for zone 5, 175-195°C for zone 6, 175-195°C for zone 7, 170-190°C for zone 8, 170-190°C for zone 9, 170-190°C for zone 10, 170-185°C for zone 11, and 165-185°C for zone 12. The screw length-to-diameter ratio used in twin-screw melt extrusion is 42:1-52:1, the main engine screw speed is 200-400rpm, and the feeding screw speed is 20-40rpm.
[0054] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0055] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0056] Elastomer graft compatibilizer embodiment:
[0057] The extrusion temperatures of the twin-screw extruder in Examples 1-12 and Comparative Examples 1-2 are as follows: 140°C for zone 1, 150°C for zone 2, 170°C for zone 3, 180°C for zone 4, 180°C for zone 5, 185°C for zone 6, 185°C for zone 7, 180°C for zone 8, 180°C for zone 9, 180°C for zone 10, 175°C for zone 11, and 175°C for zone 12.
[0058] Example 1
[0059] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 0.6 parts of DIPP, 1 part of itaconic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, the particles are water-cooled and granulated. After homogenization, high-efficiency compatibilizer particles (i.e., elastomer grafted compatibilizer) are obtained. The grafting rate of the compatibilizer measured after purification is 0.667%.
[0060] Example 2
[0061] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 0.6 parts of DIPP, 3 parts of itaconic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 0.806%.
[0062] Example 3
[0063] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 0.6 parts of DIPP, 5 parts of itaconic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 1.30%.
[0064] Example 4
[0065] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 0.6 parts of DIPP, 7 parts of itaconic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 1.09%.
[0066] Example 5
[0067] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 0.6 parts of DIPP, 9 parts of itaconic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 1.14%.
[0068] Example 6
[0069] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 0.2 parts of DIPP, 5 parts of itaconic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 0.436%.
[0070] Example 7
[0071] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 0.4 parts of DIPP, 5 parts of itaconic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 0.772%.
[0072] Example 8
[0073] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 0.8 parts of DIPP, 5 parts of itaconic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 1.089%.
[0074] Example 9
[0075] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 1 part of DIPP, 5 parts of itaconic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 1.129%.
[0076] Example 10
[0077] According to the following mass parts: 100 parts of POE and 1 part of epoxidized soybean oil are mixed evenly, and then 0.6 parts of BIBP, 5 parts of itaconic anhydride and 3 parts of α-methylstyrene are added and mixed evenly, and then added into a grafted twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 1.032%.
[0078] Embodiment 11
[0079] According to the following mass parts: 100 parts of OBC and 0.5 parts of white oil are mixed evenly, and then 0.6 parts of DTBP, 5 parts of itaconic anhydride and 0.5 parts of MAH are added and mixed evenly, and then added into a grafted twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The grafting rate of the compatibilizer measured after purification is 0.928%.
[0080] Example 12
[0081] According to the following mass parts: 100 parts of SEBS and 2 parts of paraffin oil are mixed evenly, and then 0.6 parts of TBPA, 5 parts of itaconic anhydride and 0.5 parts of α-methylstyrene are added and mixed evenly, and then added into a grafted twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The grafting rate of the compatibilizer measured after purification is 0.976%.
[0082] Comparative Example 1
[0083] According to the following mass parts: 100 parts of SEBS and 1 part of epoxidized soybean oil are mixed evenly, and then 0.6 parts of DIPP, 5 parts of maleic anhydride and 1 part of BA are added and mixed evenly, and then added into a twin-screw extruder for melt blending reaction extrusion. The screw length-to-diameter ratio used in the twin-screw melt extrusion is 48:1, and the screw speed is 300 rpm. After extrusion, water cooling and granulation are carried out, and high-efficiency compatibilizer particles are obtained after homogenization. The compatibilizer grafting rate measured after purification is 0.579%.
[0084] Comparative Example 2
[0085] The method is the same as in Example 3, except that the monomer BA is missing. Figure 2a and Figure 2b As shown, the grafting rate of Comparative Example 1 and Example 3 can be obtained. Itaconic anhydride is used as the first grafting monomer, and the grafting rate is 1.3%, which is significantly higher than that of maleic anhydride as the first grafting monomer (the grafting rate is only 0.579%). At the same time, as the content of itaconic anhydride and the content of initiator increase, the grafting rate shows a trend of first rising and then maintaining stability. The highest grafting rate is 0.6% initiator DIPP and 5% itaconic anhydride. From Examples 10-12, it can be seen that this method is also applicable to the grafting of itaconic anhydride on POE and OBC elastomers.
[0086] Table 1 Raw materials and test results of Examples 1-12 and Comparative Example 1
[0087]
[0088]
[0089] Application examples of high impact and high toughness bio-based nylon composite materials
[0090] The extrusion temperatures of the twin-screw extruder in Application Examples 1-4 and Comparative Examples 1-3 are 140°C for zone 1, 230°C for zone 2, 240°C for zone 3, 250°C for zone 4, 260°C for zone 5, 260°C for zone 6, 260°C for zone 7, 260°C for zone 8, 250°C for zone 9, 250°C for zone 10, and 245°C for zone 11.
[0091] Application Example 1
[0092] 100 parts of PA56, 17.5 parts of SEBS, 2.5 parts of ITA-g-SEBS (Example 3), and 0.2 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 rpm and the main feeding speed to 50 rpm to obtain a SEBS toughened PA56 composite material.
[0093] Application Example 2
[0094] 100 parts of PA56, 15 parts of SEBS, 5 parts of ITA-g-SEBS (Example 3), and 0.2 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 rpm and the main feeding speed to 50 rpm to obtain a SEBS toughened PA56 composite material.
[0095] Application Example 3
[0096] 100 parts of PA56, 10 parts of SEBS, 10 parts of ITA-g-SEBS (Example 3), and 0.2 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 rpm and the main feeding speed to 50 rpm to obtain a SEBS toughened PA56 composite material.
[0097] Application Example 4
[0098] 100 parts of PA56, 20 parts of ITA-g-SEBS (Example 3), and 0.2 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300RPM and the main feeding speed to 50rpm to obtain a SEBS toughened PA56 composite material.
[0099] Application Comparative Example 1
[0100] 100 parts of PA56, 20 parts of SEBS, and 0.2 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300RPM and the main feeding speed to 50RPM to obtain a SEBS toughened PA56 composite material.
[0101] Application Comparative Example 2
[0102] 100 parts of PA56, 15 parts of SEBS, 5 parts of compatibilizer of comparative example 1, and 0.2 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 rpm and the main feeding speed to 50 rpm to obtain a toughened PA56 composite material.
[0103] Application Comparative Example 3
[0104] 100 parts of PA56, 15 parts of SEBS, 5 parts of the compatibilizer of comparative example 2, and 0.2 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 rpm and the main feeding speed to 50 rpm to obtain a toughened PA56 composite material.
[0105] In order to facilitate the comparison of toughening and compatibility effects, the present invention measured the impact strength of untoughened pure PA56 to be 5.25 kJ / m 2 , the elongation at break is 3.28%, and the tensile strength and tensile modulus are 73.4MPa and 2842.3MPa respectively.
[0106] like Figure 3a As shown in the figure, by comparing the comparative example 1 with the application examples 1-5, it can be seen that the toughening effect of pure SEBS on nylon 56 is poor, and the impact strength and elongation at break are not significantly improved. At the same time, as the proportion of SEBS-g-ITA increases, the impact strength can be increased to 63.8 kJ / m 2 , which is more than 10 times that of pure PA56 and pure SEBS toughened PA56. Comparison of comparative examples 2-3 with application example 3 shows that the toughening effect of MAH or the solution without adding the third monomer is significantly worse than that of the toughening compatibilizer in application example 3.
[0107] like Figure 3b As shown in the figure, the tensile strength and tensile modulus of nylon 56 after toughening and volume expansion decreased slightly, but still maintained a high value. After toughening and volume expansion, the tensile strength can be maintained above 52MPa, and the tensile modulus can be maintained above 1700MPa.
[0108] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0109] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A high-impact and high-toughness bio-based nylon composite material, characterized in that: The raw materials for preparing the nylon composite material include the following components calculated by weight: 100 parts of bio-based nylon, 0-30 parts of toughening elastomer, 0.1-30 parts of elastomer grafting compatibilizer and 0.2-0.6 parts of antioxidant; wherein the elastomer grafting compatibilizer is obtained by grafting modified elastomer with itaconic anhydride and a third monomer; the third monomer includes any one or more combinations of butyl acrylate, α-methylstyrene and maleic anhydride.
2. The high-impact and high-toughness bio-based nylon composite material according to claim 1, characterized in that: The raw materials for preparing the nylon composite material include the following components calculated by weight: 100 parts of bio-based nylon, 0-30 parts of toughening elastomer, 0.1-30 parts of elastomer grafting compatibilizer, 0.1-0.3 parts of antioxidant 1010 and 0.1-0.3 parts of antioxidant 168; And / or, the bio-based nylon includes any one or more combinations of PA56, PA1010, PA11, PA610, and PA410; And / or, the elastomer used in preparing the elastomer graft compatibilizer includes any one or more combinations of ethylene octene copolymer, styrene-hydrogenated butadiene-styrene copolymer, and olefin block copolymer; And / or, the toughening elastomer is the same as the elastomer used to prepare the elastomer grafted compatibilizer.
3. The high-impact and high-toughness bio-based nylon composite material according to claim 1, characterized in that: The preparation method of the elastomer graft compatibilizer comprises: uniformly mixing an elastomer, a peroxide initiator, itaconic anhydride, a third monomer and a dispersing oil, and then inputting the obtained materials into a twin-screw extruder for melt blending, dynamic reaction extrusion, pelletizing and homogenization to obtain the elastomer graft compatibilizer.
4. The high-impact and high-toughness bio-based nylon composite material according to claim 3, characterized in that: The mass ratio of the elastomer, the peroxide initiator, the itaconic anhydride, the third monomer and the dispersing oil is 100: 0.2-1: 1-9: 0.5-3: 0.5-2; And / or, the elastomer includes any one or more combinations of ethylene octene copolymer, styrene-hydrogenated butadiene-styrene copolymer, and olefin block copolymer; And / or, the peroxide initiator includes any one or more of 2,4-di-tert-butyl peroxide isopropyl benzene, diisopropyl peroxydicarbonate, di-tert-butyl peroxide, and tert-butyl peroxyacetate; And / or, the dispersing oil includes any one or more combinations of self-raising oil, epoxidized soybean oil and paraffin oil.
5. The method for preparing a high-impact and high-toughness bio-based nylon composite material according to any one of claims 1 to 4, characterized in that: include: The bio-based nylon, toughening elastomer, elastomer grafting compatibilizer and antioxidant are mixed evenly, and then the obtained materials are input into a twin-screw extruder for melt blending extrusion and granulation treatment to obtain a high-impact and high-toughness bio-based nylon composite material.
6. The preparation method according to claim 5, characterized in that: The process parameters adopted by the twin-screw extruder include: the temperature of zone 1 is 130-150°C, the temperature of zone 2 is 220-240°C, the temperature of zone 3 is 230-250°C, the temperature of zone 4 is 240-270°C, the temperature of zone 5 is 245-265°C, the temperature of zone 6 is 245-265°C, the temperature of zone 7 is 245-265°C, the temperature of zone 8 is 240-260°C, the temperature of zone 9 is 240-260°C, the temperature of zone 10 is 245-260°C, the temperature of zone 11 is 245-260°C, the length-to-diameter ratio of the screw adopted is 42:1-52:1, the screw speed is 200-400rpm, and the feeding frequency is 50-70Hz.
7. An elastomer graft compatibilizer, characterized in that: The raw materials for preparing the elastomer graft compatibilizer include the following components: elastomer, peroxide initiator, itaconic anhydride, a third monomer and dispersing oil; wherein the third monomer includes any one or more combinations of butyl acrylate, α-methylstyrene and maleic anhydride.
8. The elastomer graft compatibilizer according to claim 7, characterized in that: The raw materials for preparing the elastomer graft compatibilizer include the following components calculated by weight: 100 parts of elastomer, 0.2-1 parts of peroxide initiator, 1-9 parts of itaconic anhydride, 0.5-3 parts of a third monomer and 0.5-2 parts of dispersing oil; And / or, the elastomer includes any one or more combinations of ethylene octene copolymer, styrene-hydrogenated butadiene-styrene copolymer, and olefin block copolymer; And / or, the peroxide initiator includes any one or more of 2,4-di-tert-butyl peroxide isopropyl benzene, diisopropyl peroxydicarbonate, di-tert-butyl peroxide, and tert-butyl peroxyacetate; And / or, the itaconic anhydride is prepared by dehydrating agricultural and sideline products such as starch, sucrose, sawdust or straw through biological fermentation; And / or, the dispersing oil includes any one or more combinations of self-raising oil, epoxidized soybean oil and paraffin oil.
9. The method for preparing the elastomer graft compatibilizer according to claim 7 or 8, characterized in that: include: The elastomer, peroxide initiator, itaconic anhydride, the third monomer and the dispersing oil are uniformly mixed, and then the obtained materials are input into a twin-screw extruder for melt blending, dynamic reaction extrusion, pelletizing and homogenization to obtain an elastomer graft compatibilizer.
10. The preparation method according to claim 9, characterized in that: The process parameters adopted by the twin-screw extruder include: the temperature of zone 1 is 130-150°C, the temperature of zone 2 is 140-160°C, the temperature of zone 3 is 160-180°C, the temperature of zone 4 is 170-190°C, the temperature of zone 5 is 170-190°C, the temperature of zone 6 is 175-195°C, the temperature of zone 7 is 175-195°C, the temperature of zone 8 is 170-190°C, the temperature of zone 9 is 170-190°C, the temperature of zone 10 is 170-185°C, the temperature of zone 11 is 170-185°C, the temperature of zone 12 is 165-185°C, the length-to-diameter ratio of the screw adopted is 42:1-52:1, the speed of the main engine screw is 200-400rpm, and the speed of the feeding screw is 20-40rpm.
Citation Information
Patent Citations
Low-temperature-resistant polyolefin grafted maleic anhydride flexibilizer used for nylon and preparation method of flexibilizer
CN108129833A
Starch master batch composition, starch master batch and preparation method of starch master batch
CN111808330A
Super-flexible itaconic anhydride polybutadiene modified polyolefin material as well as preparation method and application thereof
CN117534842A
Viton seal compatible dispersant and lubricating oil composition containing same
US5188745A